How the interannual and seasonal variability in connectivity to ITF and its relation to ENSO events in the Halmahera Sea: A modeling approach and observation - Lubis, Muhammad Zainuddin; Hu, Song; Simanjuntak, Andrean V.H.; Dwinovantyo, Angga; Arnold, Ekoué Ewane Blaise; Kausarian, Husnul; Jamjareegulgarn, Punyawi; Suryadarma, Made Wedanta (My University, 2026)
Understanding circulation dynamics in the Halmahera Sea (HS) is essential for clarifying the interactions between El Niño and La Niña events and ITF variability, which significantly impacts the global climate. Despite studies on air-sea interactions in the HS, gaps remain regarding interannual and seasonal variability, leading to uncertainties in understanding ocean circulation and throughflow dynamics. Specifically, there is a lack of understanding of how seasonal temperature and salinity shifts influence the strength and direction of ocean currents in the HS region. This study investigated how temperature and salinity variations during interannual and different seasons affect ocean current patterns in the HS. We used the CROCO model from 2019 to 2023 and observed it in September 2021. Our findings indicate distinct interannual patterns in SST, with the northwest monsoon SST ranging from approximately 28.3–29.8°C and the southeast monsoon SST ranging from approximately 26.8–29.0°C. The SSS varied between approximately 34.1 and 34.6 PSU, with the maximum mean water mass transport in the subsurface recorded at −0.5479 ± 0.6583 Sv at 0.5°S, indicating transport toward the Banda Sea. The SSH ranged from ∼0.69 to ∼0.73 m in the northwest and ∼0.66 to ∼0.69 m in the southeast monsoon. The densities at the surface, subsurface, and intermediate layers were 22.5, 25.5, and 26.5 σѳ. This research advances our understanding of the factors affecting HS circulation dynamics and their responses to El Niño and La Niña events, paving the way for Indo-Pacific water exchange studies.
Keywords: El Nino and La Niña events; Halmahera Sea (HS); Indonesian Throughflow (ITF); Ocean circulation and dynamics; SSS and SSH; SST